Antidepressant-Like Effects of Chronic Guanosine in the Olfactory Bulbectomy Mouse Model - Almeida, Roberto Farina; Nonose, Yasmine; Ganzella, Marcelo; Loureiro, Samanta Oliveira; Rocha, Andréia; Machado, Daniele Guilhermano; Bellaver, Bruna; Fontella, Fernanda Urruth; Leffa, Douglas T.; Pettenuzzo, Letícia Ferreira; Venturin, Gianina Teribele; Greggio, Samuel; et al. (Frontiers in Psychiatry, 2021)
Major Depressive Disorder (MDD) leads to pervasive changes in the health of afflicted patients. Despite advances in the understanding of MDD and its treatment, profound innovation is needed to develop fast-onset antidepressants with higher effectiveness. When acutely administered, the endogenous nucleoside guanosine (GUO) shows fast-onset antidepressant-like effects in several mice models, including the olfactory bulbectomy (OBX) rodent model. OBX is advocated to possess translational value and be suitable to assess the time course of depressive-like behavior in rodents. This study aimed at investigating the long-term behavioral and neurochemical effects of GUO in a mice model of depression induced by bilateral bulbectomy (OBX). Mice were submitted to OBX, and after 14 days of recovery received daily (ip) administration of 7.5mg/kg GUO or 40mg/kg imipramine (IMI) for 45 days. GUO and IMI reversed the OBX-induced hyperlocomotion and recognition memory impairment, hippocampal BDNF increase and redox imbalance (ROS, NO and GSH levels). GUO also mitigated the OBX-induced hippocampal neuroinflammation (IL-1, IL-6, TNF-α, INF-γ, and IL-10). Brain microPET imaging ([18F]FDG) shows that GUO also prevented the OBX-induced increase in hippocampal FDG metabolism. These results provide additional evidence for GUO antidepressant-like effects, associated with beneficial neurochemical outcomes relevant to counteract depression.